A Brief Review on Nanoparticles: Type of Platforms, Biological synthesis & Evaluation - AVINASH; Arpita Singh; Swarnima Pandey; Mohd Aqil Siddiqui; Nitish Kumar (International Journal of Indigenous Herbs and Drugs, 2021)
Nanoparticles refers to as particulate dispersions or solid particles with a size in the range of 10-1000nm. The nanoparticles have been used to alter the physical approach and improve the pharmacokinetic and pharmacodynamic properties of many type of drug molecules. They have significant advantages in conventional drug delivery in form of  high specificity, high stability, high drug carrying capacity, control release ability, possibility occurs  to different rout of administration and having a capability to deliver hydrophobic and hydrophilic drug molecules. This review focuses on type, preparation and evaluation of nanoparticles.